2009
DOI: 10.1016/j.drugalcdep.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Promoting abstinence from cocaine and heroin with a methadone dose increase and a novel contingency

Abstract: To test whether a combination of contingency management and methadone dose increase would promote abstinence from heroin and cocaine, we conducted a randomized controlled trial using a 2 X 3 (Dose X Contingency) factorial design in which dose assignment was double-blind. Participants were 252 heroin-and cocaine-abusing outpatients on methadone maintenance. They were randomly assigned to methadone dose (70 or 100 mg/day, double blind) and voucher condition (noncontingent, contingent on cocaine-negative urines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 37 publications
(45 reference statements)
6
45
0
Order By: Relevance
“…As argued elsewhere, our rat model of relapse/incubation after choice-based voluntary abstinence is analogous to the human condition of relapse to drug use after termination of contingency management (Caprioli et al, 2015a). Regarding the 'translational' value of our new model, the data on lack of sex differences in both the efficacy of our choice-based procedure in inhibiting drug selfadministration and relapse after cessation of 'contingency management' agree with the lack of gender differences in the efficacy of contingency management or the high relapse rates after treatment cessation in humans (Epstein et al, 2009;Lussier et al, 2006;Roll et al, 2013).…”
Section: Clinical Implications and Future Research Directionssupporting
confidence: 55%
“…As argued elsewhere, our rat model of relapse/incubation after choice-based voluntary abstinence is analogous to the human condition of relapse to drug use after termination of contingency management (Caprioli et al, 2015a). Regarding the 'translational' value of our new model, the data on lack of sex differences in both the efficacy of our choice-based procedure in inhibiting drug selfadministration and relapse after cessation of 'contingency management' agree with the lack of gender differences in the efficacy of contingency management or the high relapse rates after treatment cessation in humans (Epstein et al, 2009;Lussier et al, 2006;Roll et al, 2013).…”
Section: Clinical Implications and Future Research Directionssupporting
confidence: 55%
“…Another is that we cannot be certain that the findings are generalizable to CM based on other types of reinforcers, such as vouchers. In fact, in a separate study using vouchers (Epstein, Schmittner, Schroeder, & Preston, 2003), we found that splitting the vouchers between reinforcement of cocaine and opiate abstinence without a bonus element for simultaneous abstinence appeared to enhance opiate abstinence at the expense of cocaine abstinence. Direct comparison in a single randomized trial would be necessary to resolve this seeming discrepancy and determine the role of the bonus contingency.…”
Section: Discussionmentioning
confidence: 89%
“…This report is based on a retrospective analysis of data from 659 patients consecutively admitted to any of 3 clinical trials evaluating the efficacy of combining contingency management and methadone maintenance for dual cocaine and heroin use (Epstein et al, 2005;Epstein et al, 2003). The trials were conducted at an outpatient treatment research clinic in Baltimore, MD.…”
Section: Participants and Settingmentioning
confidence: 99%